Impact of Child Labour on Education in Bugujju Village Mukono District - Mwembebezi, Rachael (Mukono : Uganda Christian University, 2009)
Discriptive Cataloguing Uganda Christian University BCDCM
Includes referece and appendix
Keywords: Child Labour